Retailer-run resale market and optimal returns and resale policy - Lee, Chang Hwan; Rhee, Byong Duk (European Journal of Operational Research, 2018)
This study investigates a retailer's motivation for running its own resale market, and derives the optimal returns and resale policy for the retailer. Consumers often make purchase decisions without complete information on the product, and may not buy the product unless they can dispose of it to recover some of the cost after purchase. A retailer's provision of returns allowance functions as a form of insurance, encouraging consumers to purchase the product from the retailer; however, the size of consumer returns has soared and is eroding the manufacturer's and retailer's profits significantly. In this study, we consider consumers’ resale decisions, as well as returns decisions, concurrently in disposing of the product after purchase. The findings suggest that a retailer should offer resale service and give all the revenue from selling a used product to the consumer who demands the resale. By so doing, the retailer induces consumers to resell their product instead of engaging in more costly product returns. Therefore, the retailer-run resale market not only increases the price and sales of new products but also decreases the size of consumer returns. The resale market benefits the manufacturer as well, due to the increase in order quantity.
Keywords: Complete information; Market benefits; Order quantity; Product returns; Product value; Purchase decision; Used product; Product returns policy; Resale policy; Retailer-run resale market; Supply chain management; Uncertainty of product value